KI67 PROLIFERATION INDEX AND ITS ASSOCIATION WITH DIFFUSE LARGE B-CELL LYMPHOMA STAGE - Ramkita, Nora; Krisna Murti; Heni Maulani; Iche Andriyani Liberty (Majalah Kedokteran Sriwijaya, 2024)
Diffuse large B-cell lymphoma (DLBCL) is the most common invasive subtype of NHL, with an increasing incidence of 150,000 new cases worldwide each year. The Ann Arbor staging system categorizes DLBCL into four stages. Ki67 immunohistochemical examination is a proliferation marker and is used as a prognostic and predictive marker in various organs. This study was conducted to determine the relationship between the Ki67 index, clinicopathological features, and DLBCL stage.This study is an observational analytic study with a cross-sectional retrospective study design using 40 samples of slide archives of DLBCL cases. The sampling method was purposive sampling of DLBCL specimens from January 2019 to December 2021. Staging data is obtained through medical records and based on Ann Arbor staging system assessments. The Ki67 index was assessed on tumor hot spots and averaged in percentage. Categorized as low and high, with a cut-off point value of 85%. The relationship between the Ki67 index and stage was analyzed using Fisher's exact test.Fisher's exact test showed a significant association between the Ki67 index and the DLBCL stage, with a p-value of 0.002. There was no significant association between age, gender, location, and subtype, with p-values of 0.201, 0.607, 0.132, and 0.105, respectively.There is a significant correlation between the Ki67 index (>85%) and the DLBCL stage.